Morphological and molecular analyses revealed two new species of Begonia sect. Baryandra in the Eastern Mindanao Biodiversity Corridor, Philippines - Bucay, Mark Angelo C.; Tandang, Danilo N.; Chen, Hong-Wun; Tsai, Li-Wei; Rubite, Rosario R.; Chung, Kuo-Fang (Phytotaxa, 2025)
Two new species of Begonia section Baryandra from the province of Davao Oriental, part of the Eastern Mindanao Biodiversity Corridor (EMBC), Philippines are described and illustrated. We compared these species with two other species found in EMBC. Begonia dorisiae resembles B. amparoae but is distinct by tomentose hairs with a bulbous base on the petioles and abaxial side of the lamina. Begonia medinae resembles B. elmeri, both of which are the only peltate Mindanao species to date but is distinct mainly on the dense pilose hairs on its lamina, petioles and peduncles. Analyses of the Internal Transcribed Spacer (ITS1, ITS2 and 5.8S gene) sequences of these Eastern Mindanao species, combined with other 45 Philippine sect. Baryandra species and 10 other Asian species support the distinction of the two new species from their congeners. The phylogenetic placement of these plants alongside other Philippine species can further shed light on the intricate biogeographic patterns of Philippine wildlife, especially on areas less studied such as EMBC.